Tool path generation for five-axis machining of impellers - Park, S; Chang, M; Ju, JH (TAYLOR & FRANCIS LTD, 1999)
This paper proposes a new tool path generation method for machining impellers with five-axis machines. Using the geometric characteristics of impellers, the proposed method first computes the tool path in the cylindrical coordinates and then converts it into the cartesian coordinates. The proposed method is simpler, more efficient, and requires less user interactions than known methods. Collision avoidance and optimum cutting condition issues are also addressed in this paper.
Keywords: 5-AXIS